Application of anthocyanin extract from butterfly pea flower (Clitoria ternatea) as a freshness indicator : Aplikasi ekstrak antosianin bunga telang (Clitoria ternatea) sebagai indikator kesegaran - Assyifa, Cut Fatima; Franella, Intan Ade; Halqiah, Fanny; Sulaiman, Ismail; Yunita, Dewi (Universitas Slamet Riyadi Surakarta, 2025)
Chicken and processed products like dimsum are susceptible to rapid spoilage due to their high water and nutrient content. This makes it difficult for consumers to directly assess a packaged product's freshness. To address this, a novel smart packaging solution using a biodegradable film infused with anthocyanin extract from butterfly pea flowers (Clitoria ternatea) as a visual freshness indicator was developed. The primary objective of this research was to evaluate the effect of three different anthocyanin concentrations (3%, 5%, and 7%) on the film's physical properties and its ability to change color in response to spoilage over a three-day storage period. The research results showed that the film with a 7% anthocyanin concentration had the best physical properties, with a thickness of 0.092 mm, a tensile strength of 8.66 MPa, 14.99% elongation, 62.59% water resistance, and 100% biodegradation. The anthocyanins successfully changed color in response to the freshness level of both chicken meat and dimsum throughout the storage period.